Intranasal MMI-0100 Attenuates Aβ1−42- and LPS-Induced Neuroinflammation and Memory Impairments via the MK2 Signaling Pathway - Jiang, JinHong; Wang, Zhe; Liang, XueYa; Nie, YaoYan; Chang, Xin; Xue, HongXiang; Li, Shu; Min, Chang (Frontiers in Immunology, 2019)
Background Accumulating evidence suggests that inhibiting neuroinflammation as a potential target in therapeutic or preventive strategies for Alzheimer’s disease (AD). MAPK-activated protein kinase II (MK2), downstream kinase of p38 mitogen activated protein kinase (MAPK) p38 MAPK, was unveiled as a promising option for the treatment of AD. Increasing evidence points at MK2 as involved in neuroinflammatory responses. MMI-0100, a cell-penetrating peptide inhibitor of MK2, exhibits anti-inflammatory effects, and is in current clinical trials for the treatment of pulmonary fibrosis. Therefore, it is important to understand the actions of MMI-0100 in neuroinflammation. Methods The mouse memory function was evaluated using novel object recognition (NOR) and object location recognition (OLR) tasks. Brain hippocampus tissue samples were analyzed by quantitative PCR, western blotting, and immunostaining. Near-infrared fluorescent and confocal microscopy experiments were used to detect the brain uptake and distribution after intranasal MMI-0100 application. Results Central MMI-0100 was able to ameliorate the memory deficit induced by Aβ1-42 or LPS in novel object and location memory tasks. MMI-0100 suppressed LPS-induced activation of astrocytes and microglia, and dramatically decreased a series of pro-inflammatory cytokines such as TNF-α, IL-6, IL-1β, COX-2 and iNOS via inhibiting phosphorylation of MK2, but not ERK, JNK and p38 in vivo and in vitro. Importantly, one of the reasons for failure of macromolecular protein or peptide drugs in the treatment of AD can not across blood-brain barrier. Our data showed that intranasal administration of MMI-0100 significantly ameliorates the memory deficit induced by Aβ1-42 or LPS. Near-infrared fluorescent and confocal microscopy experiments results showed that a strong fluorescent signal, coming from mice brains, was observed at 2 h after nasal applications of Cy7.5-MMI-0100. However, brains from control mice treated with saline or Cy7.5 alone displayed no significant signal. Conclusions MMI-0100 attenuates Aβ1-42- and LPS-induced neuroinflammation and memory impairments via the MK2 signaling pathway. Meanwhile, these data suggest that MMI-0100/MK2 system may provide a new potential target for treatment of AD.